Design of a ready-to-eat child food fortified with pea-based iron (Pisum sativum) - Villaquirán, Zulma; Burbano, Paola; Osorio-Mora, Oswaldo; Cerón-Cardenas, Andrés Felipe; Bucheli-Jurado, Mauricio Alexander (Universidad y Salud, 2018)
Introduction: Iron deficiency is one of the most prevalent nutritional problems at the global level which mainly affects the vulnerable population as children under 5 years of age. Fortified foods of child consumption are part of the intervention strategies, which are made from the mixture of ingredients such as cereals, fruits, legumes, among others. Pea is a legume that can be used in order to take advantage of its nutritional properties. Objective: To design a ready-to-eat child food with peas (Pisum sativum), fortified with iron and sanitized by pasteurization. Materials and methods: The appropriate percentage of peas in the food was selected by sensory analysis. The selection of iron salt was made by physicochemical and sensory analysis using ferrous sulphate and chelate iron. Subsequently, the growth of mesophilic microorganisms was evaluated in order to select the pasteurization heat treatment. The useful life evaluation was carried out through sensory tests. Finally, the physico-chemical, compositional and microbiological evaluation of the sanitized food was implemented. Results: The addition of peas in percentages not greater than 6.5% within the food formulation was acceptable for parents of children under 5. On the other hand, the selected salt to generate less changes on the color and acidity of the food during storage was chelate iron. The results of heat treatment showed that for reducing the initial concentration of mesophiles and obtaining a good quality food according to the Colombian regulations in force, it was necessary to submit the food to 85 °C for 13 minutes (0.45 D), which managed to maintain the initial quality of the food for 12 days under refrigeration. Conclusions: The developed food complies with the sensory and microbiological criteria demanded in the Colombian regulations in force and is suitable for consumption. Besides, it can be catalogued as high in iron and a good source of protein, contributing with 25% and 15% of the daily recommendation in Colombia, respectively.